Kebijakan Pemimpin Pondok Pesantren Hidayaul Mubtadi’in Kembang Singosari Malang Dalam Pengembangan Pendidikan Formal - Mirza Nur Alimi (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2020)
In educational institutions, both formal and non-formal, the policy of a leader becomes the center of discussion and attention of experts, namely in terms of science itself and other sciences. Based on these facts, especially those related to the policies of the boarding school leaders have the right to all authority and responsibility that exist in the foundation, especially in formal education under its auspices. Therefore it is necessary to re-examine the policies of the Islamic boarding school leaders in the development of formal education, so that in the development of education it is not only in Islamic boarding school education.          Based on the cases taken, the formulation of the research problem is to describe how the policies of the leader of the Islamic boarding school Hidayaul Mubtadi'in Kembang in the development of formal education, and to describe how the policy making process of the leader of the Islamic boarding school Hidayaul Mubtadi'in Kembang in the development of formal education. This research is a qualitative research. Data collection was carried out by conducting observations, interviews and documentation. Data analysis was carried out by collecting data which was then selected and simplified according to the research findings, by presenting data that could be drawn conclusions. In this study, the data validity checking techniques used were credibility, transfrability, dependability, and confirmability              The results of this study can be concluded that: 1) The policy of the leader of the Islamic boarding school Hidayatul Mubtadi'in Kembang in the development of formal education is made in a way that is always side by side, in line and continues to collaborate with the school. the policies are also very good, and very supportive of the existing programs in schools. Planning any policies before the start of each year of the education period. Planning references are the government's vision and mission, vision and mission of the institutions and pesantren programs. Policy efforts include meetings to evaluate development programs, strengthening collaboration, and building creativity and innovation in entrepreneurship. Policies are made on the basis of deliberation and the existence of responsible parties, namely caregivers, administrators, school principals and all WAKA, 2) The process of making policies for the leadership of the Hidayatul Mubtadi'in Kembang Islamic boarding school in the development of formal education, namely receiving input and suggestions by considering conditions and situations, communicate intensively, and use the alternative dar'ul mafasid muqoddamu 'ala jalbil masholih in the rules of ushul fiqh, accompanied by holding meetings and deliberations.